2015
DOI: 10.1080/0972060x.2014.960277
|View full text |Cite
|
Sign up to set email alerts
|

Constituents of the Essential Oils of the Leaf and Root ofEryngium foetidumL. from Two Locations in India

Abstract: Essential oils of the leaf and root of Eryngium foetidum L. from Port Blair (Andaman and Nicobar) and Nadugani (Tamil Nadu) in India were investigated by GC and GC-MS analyses. The oils of the leaf and root from the two locations were found to contain alkanes, alkanals, alkenals, fatty acids, aromatic aldehydes, mono-, sesqui-and diterpenes, aromatic aldehydes and terpene aldehyde esters. The main components of the oil of the leaf from Port Blair were identified as a trimethyl benzaldehyde (16.5 %), dodecanal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 21 publications
0
15
0
2
Order By: Relevance
“…Chandrika et al [ 17 ] reported a higher DPPH radical activity (96.674% inhibition at 50 µg/mL, IC 50 value of 22.14) for the Indian E. foetidum leaf oil compared with the Nigerian leaf oil ( Table 1 ); however, the authors did not present the chemical profile of the leaf oil. Previous investigation on E. foetidum leaf oils from India revealed the occurrence of muurola-4,10(14)-diene-1-ol (10.2%), hexahydrofarnesylacetone (5.5%), palmitic acid (4.6%) and phytol (4.9%) which were not identified in the Nigerian samples [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…Chandrika et al [ 17 ] reported a higher DPPH radical activity (96.674% inhibition at 50 µg/mL, IC 50 value of 22.14) for the Indian E. foetidum leaf oil compared with the Nigerian leaf oil ( Table 1 ); however, the authors did not present the chemical profile of the leaf oil. Previous investigation on E. foetidum leaf oils from India revealed the occurrence of muurola-4,10(14)-diene-1-ol (10.2%), hexahydrofarnesylacetone (5.5%), palmitic acid (4.6%) and phytol (4.9%) which were not identified in the Nigerian samples [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…The essential oils of 36 Eryngium species have already been studied and the sample oils can be divided into two main chemical compositions according to their main components. The first group is characterized by oxygenated compounds including sesquiterpenes such as γ ‐cadinen‐15‐al, spathulenol, sesquicineole, α ‐bisabolol, and cis ‐chrysanthenyl acetate, as well as nonterpenic compounds such as trimethylbenzaldehyde, ( E )‐2‐dodecenal, linear acids, and polyacetylenes . The second group includes sample oils with terpenic hydrocarbon compounds such as germacrene D, bicyclogermacrene, γ ‐muurolene, and trans ‐caryophyllene …”
Section: Introductionmentioning
confidence: 99%
“…Note that the chemical composition of the chicory leaf and root is similar, because Chandrika et al [ 58 ], Thomas et al [ 1 ], and Rodrigues et al [ 5 ] identified (2E)-2-dodecenal in the leaves and roots of E . foetidum , in addition to 13-tetradecenal, trans -2-tetradecenal, 2,3,4-trimethylbenzaldehyde [ 5 ], 2,4,5-trimethylbenzaldehyde, dodecanal [ 1 ], 1, trimethylbenzaldehyde, τ -cadinol, and α -cadinol [ 58 ].…”
Section: Chemical Profilementioning
confidence: 97%